Inguinal hernia with a Meckel’s strangulated diverticulum; Littre’s hernia. - Perrone, Luis; Laviña, Raúl; Pamparato, Mario; González Moreno, Yamandú; Goycoechea, Walter (Cirugía del Uruguay, 1983)
One case ofLittre's hernia is present ed. Anhist orical review is done. Sorne considerations about more frequent complicat ions and treatment are done.